Analysis of Customer Satisfaction with Service Quality UD Mete Mubaraq Lombe in Kendari City - La Ode Nurlan; Sitti Aida Adha Taridala; Abdul Gafaruddin (International Journal of Technology and Education Research, 2025)
This study aims to analyze consumer satisfaction with the quality of UD Mete Mubaraq Lombe service in Kendari City. The sampling technique used in this study is non-probability sampling in the form of accidental sampling. The number of samples taken in this study was 38 people. The data analysis used to answer the problems in this study uses the Importance Performance Analysis (IPA) method. Importance Performance Analysis is the most commonly used method to measure consumer satisfaction levels because it has several advantages compared to other methods. The results of the study showed that the level of satisfaction with the service quality of UD Mete Mubaraq Lombe in the category was very good, all attributes with an average score of 95